2023
DOI: 10.1021/acsnano.2c07663
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Retinal Neurons Can Be Modulated by Tunable Near-Infrared Nanoparticle Sensors

Abstract: The vision of patients rendered blind by photoreceptor degeneration can be partially restored by exogenous stimulation of surviving retinal ganglion cells (RGCs). Whereas conventional electrical stimulation techniques have failed to produce naturalistic visual percepts, nanoparticle-based optical sensors have recently received increasing attention as a means to artificially stimulate the RGCs. In particular, nanoparticle-enhanced infrared neural modulation (NINM) is a plasmonically mediated photothermal neurom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
8
1
Order By: Relevance
“…Similarly, the optimal performance specifications of a nanoparticle-based retinal interface – in terms of spatial and temporal resolution, response dynamics and exposure to long and repeated stimulation – cannot be confidently specified at this stage. While the recent results reported for photothermal stimulation and inhibition of RGCs by gold nanoparticles ( Begeng et al, 2023 ) suggest that a high degree of spatial and temporal control is theoretically possible, there will almost certainly be tradeoffs, for example in terms of heat buildup during repeated stimulation. Moreover, further investigation is required to establish whether RGCs become desensitized to repetitive stimulation via nanoparticle interfaces, as has been observed for electrical stimulation with conventional retinal prostheses ( Jensen and Rizzo, 2007 ; Freeman and Fried, 2011 ; Soto-Breceda et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, the optimal performance specifications of a nanoparticle-based retinal interface – in terms of spatial and temporal resolution, response dynamics and exposure to long and repeated stimulation – cannot be confidently specified at this stage. While the recent results reported for photothermal stimulation and inhibition of RGCs by gold nanoparticles ( Begeng et al, 2023 ) suggest that a high degree of spatial and temporal control is theoretically possible, there will almost certainly be tradeoffs, for example in terms of heat buildup during repeated stimulation. Moreover, further investigation is required to establish whether RGCs become desensitized to repetitive stimulation via nanoparticle interfaces, as has been observed for electrical stimulation with conventional retinal prostheses ( Jensen and Rizzo, 2007 ; Freeman and Fried, 2011 ; Soto-Breceda et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticle-mediated retinal protheses offer an opportunity to selectively activate ON and OFF RGCs by targeting nanoparticles to different cell types. Some progress in this direction has been made by Begeng et al (2023) , where it has been shown that OFF RGCs can be preferentially inhibited using gold nanorods and long near-infrared pulses. The mechanism of inhibition during nanoparticle-enhanced infrared neuromodulation is due to the phenomenon known as thermal block, mediated by voltage-gated potassium channels suppressing action potentials at elevated temperatures ( Ganguly et al, 2019 ).…”
Section: The Retina and Its Degenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the oxidation process used to fabricate GO, the recombination of electron-hole pairs present in its basal area confers photothermal properties to the bulk material. 92,93 Nonetheless, the scaffolds containing only GO require a higher irradiance to evoke depolarization when compared to the scaffolds containing GO and AuNRs.…”
Section: Biomaterials Science Papermentioning
confidence: 99%